GEJALA CAMPUR KODE PADA PENGUNJUNG TAMAN MINI INDONESIA INDAH - Erwin Salpa Riansi (Jurnal Membaca Bahasa dan Sastra Indonesia, 2017)
This research is a qualitative descriptive study aimed to analyze and describe the form of code-mixing languages on the visitors at Taman Mini Indonesia Indah, and the factors that cause interference code. The method used in this research is descriptive qualitative, because the study conducted by researchers generate data or information to be arranged, and described and then analyzed. The technique is done in data collection which is a technique of documentation in the form of interviews and observations. Sources of data in this study is kind of spoken language, in the form of a conversation that took place between researcher and researched, while his form in the form of a taped interview. Research data transcription of the interview. Form of code-mixing is done by one of the visitors at Taman Mini Indonesia Indah, by mixing Indonesian, regional languages and foreign languages. Types of code-mixing is performed by one of the visitors named Mr. Halomoan among which the insertion elements are tangible word, phrase, word repetition, clause. There are several factors that cause interference language code that is of factors role, diverse factors, factors desire to explain and interpret.